Manajemen Kurikulum Program Tahfidz Al-Qur’an di Pondok Pesantren Salafiyah Syafi’iyah Al-Azhar Mojosari Situbondo - Siti Rohmatillah; Munif Shaleh (Program Pascasarjana Universitas Ibrahimy, 2018)
This development research aims to design the management of the Tahfidz Al-Qur'an program. This study applies the development method of Borg and Gall research. Development design is using the inverted Taba model. The seven steps of the model applied are: first, diagnosing needs; second, formulating goals; third, choose content; fourth, organize content, fifth; choose learning experience, sixth; organize learning experiences, seventh; evaluate. The development plan is then validated by experts and declared feasible for field testing.